Austerity/Immiseration Capitalism and Islamophobia — Or Twenty-First-Century Multicultural Socialism?. (January 2014) - Cole, Mike
This article is in three parts. In part one, the author begins by examining the onset of austerity/immiseration capitalism in the United Kingdom. Austerity/immiseration capitalism has witnessed the decline of state multiculturalism and increasing attempts to deflect attention away from the failures of capitalism by playing the 'race card'. At the same time, state multiculturalism has been replaced by 'muscular liberalism'. As an absolute contrast to developments in the United Kingdom, in part two of the article, he discusses anti-racist multicultural twenty-first-century socialism in the making in the Bolivarian Republic of Venezuela. In part three of the article, the author assesses what needs to be done. For a permanent solution to austerity/immiseration capitalism and Islamophobia, the author suggests, we need to learn from the Venezuelan example.